Suspected orbital myositis associated with COVID-19. (2nd November 2021) - Armstrong, Blair K.; Murchison, Ann P.; Bilyk, Jurij R.
ABSTRACT: A 44-year-old male patient developed proptosis, edema, and erythema progressing to complete ptosis and supraduction deficit 2 days after positive COVID-19 test. He failed to improve on systemic antibiotics. MRI showed thickening and T2 enhancement of the superior rectus/levator complex consistent with orbital myositis. He improved on intravenous corticosteroids and experienced continued gradual improvement on oral steroids.